Alleviating the adverse impacts of high influent ammonium on an activated sludge system by adding Fe salts and ballasted media. (15th January 2023) - Ma, Hang; Chen, Yihua; Zhu, Jiaxin; Fan, Ruisi; Chen, Zhiqiang; Meng, Liao; Liu, Tongzhou
Abstract: High influent ammonium often leads to sludge disintegration and solubilization in activated sludge systems and thereby deteriorates pollutant removal, due to the presence of free ammonium at high concentrations. The effects of adding Fe(II)/Fe(III) salts and ballasted media (magnetic powder, PAC and quartz sand) into activated sludge systems to alleviate the adverse impacts imposed by high influent ammonium were investigated in lab-scale continuously operated SBRs. When influent ammonium was approximately 500 mg N/L, the beneficial effects of Fe salts and ballasted media addition on pollutant removal were not significant, although they showed elevated aggregation of activated sludge flocs as reflected by the values of SV30 and MLVSS. When the influent ammonium concentration was increased to as high as 700 mg N/L, the pollutant removal and sludge properties in all the reactors deteriorated. Fe salts and ballasted media addition alleviated such deterioration by retaining sludge settleability and relatively stable biomass and resulted in better pollutant removal compared to no additive addition. Microbial analyses also revealed that the abundance of flocculation bacteria ( Zoogloea and Haliscomenobacter ) and nitrifiers ( Nitrosomonas and Nitrosopira ) were higher in Fe salts or ballasted media-supplemented reactors, which correlated well with the maintenance of sludge settleability and nitrification under high ammonium stress. When the influent ammonium concentration was increased to approximately 900 mg N/L, rapid collapse occurred in all reactors regardless of whether Fe salts and ballasted media were added, indicating that activated sludge systems cannot withstand such a high influent ammonium concentration. According to the continuous monitoring of pollutants removal, nitrification, and changes in sludge properties, the degree of alleviating high ammonium stress follows the order (from high to low) of magnetic powder, PAC, Fe(II), Fe(III), and quartz sand. According to an operation cost analysis, Fe(II) had the least additional cost (0.4–0.5%). The additional costs of MP and PAC were same (4–5.33%). Fe(II) was recommended based on an overall balance in technical and cost aspects. Graphical abstract: Image 1 Highlights: Additives were used to alleviate high NH4 + 's impacts to an activated sludge system. Fe(II) and Fe(III) salts, and magnetic powder, PAC and quartz sand were studied. Adding additives alleviated the deterioration led by high ammonium at ≤ 700 mg N/L. MP, PAC, or Fe salts alleviated the suppression by maintaining sludge integration. Typical filamentous bacteria and nitrifiers were elevated with additives addition.